Peace dancer - Vickers, Roy Henry, 1946-; Budd, Robert, 1976- (Northwest coast legends, 2016)
"The children of the Tsimshian village of Kitkatla love to play at being hunters, eager for their turn to join the grown-ups. But when they capture and mistreat a crow, the Chief of the Heavens, angered at their disrespect, brings down a powerful storm. The rain floods the Earth and villagers have no choice but to abandon their homes and flee to their canoes. As the seas rise, the villagers tie themselves to the top of Anchor Mountain, where they pray for days on end and promise to teach their children to value all life. The storm stops and the waters recede. From that point on, the villagers appoint a chief to perform the Peace Dance at every potlatch and, with it, pass on the story of the flood and the importance of respect"--